Effect of a Dementia Diagnosis on Survival of Older Patients After a Diagnosis of Breast, Colon, or Prostate Cancer: Implications for Cancer Care - Raji, Mukaila A. (2008)
BACKGROUND: Preexisting dementia affects cancer care. Knowledge of how dementia affects survival after a cancer diagnosis may help guide cancer care decisions. We therefore examined the associations between preexisting diagnoses of dementia and survival from breast, colon, and prostate cancer. METHODS: We conducted a retrospective cohort study of 106 061 patients aged 68 years or older diagnosed as having breast, colon, or prostate cancer, using data from the linked Surveillance, Epidemiology and End Results– Medicare database. We assessed the risks of mortality from cancer and noncancer causes, stratified by presence or absence of preexisting dementia diagnoses. Cox proportional hazards regression was used to adjust for confounding variables. RESULTS: Seven percent of our sample had preexisting dementia diagnoses. Survival after a cancer diagnosis was markedly worse in demented than in nondemented patients. Most of the excess deaths came from noncancer causes; 33.3% of those with a dementia diagnosis died within 6 months of a cancer diagnosis, compared with 8.5% of patients without dementia. Less than 17.0% of the excess mortality in patients with dementia who had breast or colon cancer was explained by a more advanced cancer stage at diagnosis. None of the excess deaths in prostate cancer was explained by stage at diagnosis. For all 3 cancers, the presence of preexisting dementia diagnoses attenuated the relationship between stage at diagnosis and survival. CONCLUSIONS: Preexisting dementia diagnoses were associated with high mortality, mostly from noncancer causes. The effect of cancer stage at diagnosis on mortality was significantly reduced in older patients with pre-cancer diagnoses of dementia.